2020
DOI: 10.21037/jtd.2019.12.98
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metformin on survival outcome of esophageal squamous cell carcinomas patients undergoing surgical resection: a multicenter retrospective study

Abstract: Background: Diabetes mellitus is a recognized risk factor for esophageal squamous cell carcinomas (ESCC), and metformin is a recognized protective factor for some gastrointestinal tumors. But knowledge is limited regarding the effect of metformin on survival outcome of ESCC patients with type 2 diabetes mellitus (T2DM). We assessed the impact of post-diagnosis metformin use on overall survival (OS) and disease-free survival (DFS) in ESCC with T2DM undergoing surgical resection.Methods: A retrospective analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…The association between metformin use and a lower mortality found in this study is consistent with 2 small studies of esophageal cancer patients ( 19 , 29 ). In contrast, 2 other studies reported no survival benefit; one included 461 esophageal cancer patients of whom 32 diabetics used metformin and 11 did not ( 20 ), and the other compared 29 diabetic metformin users with 21 nonusers in a cohort of 285 esophageal cancer patients ( 30 ).…”
Section: Discussionsupporting
confidence: 92%
“…The association between metformin use and a lower mortality found in this study is consistent with 2 small studies of esophageal cancer patients ( 19 , 29 ). In contrast, 2 other studies reported no survival benefit; one included 461 esophageal cancer patients of whom 32 diabetics used metformin and 11 did not ( 20 ), and the other compared 29 diabetic metformin users with 21 nonusers in a cohort of 285 esophageal cancer patients ( 30 ).…”
Section: Discussionsupporting
confidence: 92%